Recurrent Neck Lymphangioma in a Young Adult: Twenty-Three Years After Successful Treatment. (February 2019) - Kotsis, Thomas; Exarchos, Georgios; Metaxa, Linda; Triantos, Stylianos
Lymphangiomas are rare benign malformations of the lymphatic system, commonly present in children, over the head and neck area. Occasionally, they can grow significantly in size and especially those located over the cervical region can cause airway obstruction and become life-threatening. Recurrent lymphangiomas usually occur during the early postsurgical period and 80% of them within the first 3 to 5 years. However, in a new onset of clinical manifestations affecting the head and neck, even many years after the successful surgical treatment, a recurrent lymphangioma should be considered in the differential diagnosis. We present herein the second reported case, to our knowledge, of a recurrent left-sided neck lymphangioma in a young man, 23 years after a successful surgical treatment that initially took place 6 weeks after his birth.